UJI KUALITAS AIR MINUM DAN AIR SANITASI YANG ADA PADA UPT SPF SDN KOMPLEK IKIP - Andis Sugrani; Nuramaniyah Taufiq (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
Water is a limited natural resource whose existence is needed for the survival of all living things. Drinking water and sanitation water are clean water whose quality meets health requirements and can be drunk directly, the health requirements referred to are microbiological, physical chemistry and radio active requirements. This Community Service was carried out at UPT SPF SDN IKIP Makassar Complex which aims to find out how the quality of drinking water and sanitation water in the school environment needs to be tested which includes parameters of pH, temperature, color, turbidity, odor and taste so that it can be said that water that is clean proper to use. Based on the inspection examination of drinking water sourced from PDAM water and sanitation water involving physical parameters, namely pH, temperature, color, turbidity, odor and taste, in a condition suitable for use as drinking water and sanitation water